Influence of ultrasound determination of fetal head position on mode of delivery: a pragmatic randomized trial. (28th September 2015) - Popowski, T.; Porcher, R.; Fort, J.; Javoise, S.; Rozenberg, P.
Abstract : This article has been selected for Journal Club. Clickhere to view slides and discussion points. Abstract: Objective: To evaluate the influence of ultrasound determination of fetal head position on mode of delivery. Methods: This was a pragmatic open‐label randomized controlled trial that included women with a singleton pregnancy in the vertex presentation at ≥ 37 weeks' gestation, cervical dilation ≥ 8 cm and who received epidural anesthesia. Women were assigned randomly to undergo either digital vaginal examination (VE group) or both digital vaginal and ultrasound examinations (VE+US group) to determine fetal head position. When the ultrasound and digital vaginal findings were inconsistent in the VE+US group, the ultrasound result was used for clinical management. The primary outcome assessed was operative delivery (Cesarean or instrumental vaginal delivery), and maternal and fetal morbidity were also assessed. Results: The VE and VE+US groups included 959 and 944 women, respectively. The overall rate of operative delivery was significantly higher in the VE+US group than in the VE group: 33.7% vs 27.1%, respectively (relative risk (RR), 1.24 (95% CI, 1.08–1.43)), as was the rate of Cesarean delivery: 7.8% vs 4.9%, respectively (RR, 1.60 (95% CI, 1.12–2.28)). The rate of instrumental vaginal delivery was also higher, albeit not significantly: 25.8% in the VE+US group vs 22.2% in the VE group (RR, 1.16 (95% CI, 0.99–1.37)). Neonatal outcomes did not differ between the two groups. When analysis was restricted to instrumental vaginal deliveries only, maternal and neonatal morbidity outcomes were similar in both groups. Conclusion: Correction of fetal occiput position, determined initially by digital vaginal examination, using systematic ultrasound examination did not improve management of labor and increased the rate of operative delivery without decreasing maternal and neonatal morbidity. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd.